Enzyme-like activity of nanomaterials - S. I. Tsekhmistrenko; V. S. Bityutskyy; O. S. Tsekhmistrenko; V. M. Polishchuk; S. A. Polishchuk; N. V. Ponomarenko; Y. O. Melnychenko; M. Y. Spivak (Regulatory Mechanisms in Biosystems, 2018)
In modern conditions, nanomaterials, especially nanoparticles of metals and nonmetals, are increasingly used in various industries. Due to their unique properties, in particular, the ability of nanoparticles to exhibit an enzyme-like effect they are widely used in biology, medicine, biotechnology, the food industry and agriculture. Important advantages of nanoparticles are their size, which enables specific properties to be present: their large surface area, the ability to transfer molecules and the ability to protect them from degradation and release over a long time, the location of action and the specificity of interaction with biological structures. Nanoparticles play a special role in the processes of neutralizing the active forms of oxygen. It has been established that a number of nanoparticles, in particular, Fe, Mn, Zn, Ce, Si and Se oxides, have an enzyme-like activity mimicking that of some enzymes. By changing the degree of oxidation, these particles can regenerate and continuously catalyze the reaction of neutralizing superoxide anion radicals, thus fulfilling the function of SOD and being the first link in protecting tissues and cells from oxidative stress in physiological and pathological conditions. It is proved that nanoparticles Mn3O4, Fe3O4, Co3O4, CeO2, LaCoO3 and other elements can effectively dispose of hydrogen peroxide and other peroxides, showing catalase-like and peroxidase-like activity. Nanozymes are characterized that exhibit the activity of oxidases, peroxidases and phosphatase. The prospect of using mimetics for complex in vitro analyzes of high-sensitivity biomarker disease detection is shown. The possibility of effective multi-use of nanoparticles as antioxidants is indicated. There are good prospects for further research on properties and the use of polyfunctional particles that are easily synthesized, reliable and inexpensive. More work is needed to determine the interaction of enzymomimetics with biological molecules such as proteins, carbohydrates and lipids, and also to take into account the peculiarities of their metabolism, clearance, degradation, biocompatibility and side effects, since individual nanoparticles have the potential to be deposited in separate organs.